2022
DOI: 10.1073/pnas.2121302119
|View full text |Cite
|
Sign up to set email alerts
|

Sensing the shape of a cell with reaction diffusion and energy minimization

Abstract: Some dividing cells sense their shape by becoming polarized along their long axis. Cell polarity is controlled in part by polarity proteins, like Rho GTPases, cycling between active membrane-bound forms and inactive cytosolic forms, modeled as a “wave-pinning” reaction-diffusion process. Does shape sensing emerge from wave pinning? We show that wave pinning senses the cell’s long axis. Simulating wave pinning on a curved surface, we find that high-activity domains migrate to peaks and troughs of the surface. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…When D b is large enough, polarisation patterns can be generated and these are subject to a slow transition of the polarised area across the surface Γ. This is an intrinsic feature of equation (3) for a(x, t), as recently shown, for instance by Singh et al [17] and Miller et al [10] for the reduced surface reaction-diffusion model (5).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…When D b is large enough, polarisation patterns can be generated and these are subject to a slow transition of the polarised area across the surface Γ. This is an intrinsic feature of equation (3) for a(x, t), as recently shown, for instance by Singh et al [17] and Miller et al [10] for the reduced surface reaction-diffusion model (5).…”
Section: Discussionmentioning
confidence: 82%
“…It was suggested that the motion of the polarised patch across the domain corresponds to a minimisation of the perimeter of the interface separating the states a high and a low , under the constrain of constant polarised mass [7]. Recently, Singh et al [17] compared the reduced model equation ( 5) with a problem of perimeter minimisation with constant polarisation patch area, obtaining, for certain initial conditions, a very good agreement between the two solutions.…”
Section: Bulk Diffusion Model Reduction and Curvature-driven Polarisa...mentioning
confidence: 99%
See 1 more Smart Citation
“…The LSA may also find applications in the analysis of shape sensing of a cell. 46 Broadly, the methods outlined in the paper can be incorporated into any RD-like systems involved in the analysis of various symmetry-breaking mechanisms in cellular processes [7][8][9]31,37,47,48 where the effect of geometry can be significant. 31,49 In brief, the work can provide useful insights into controlling cell polarity by tuning the RD parameters and may shed some fundamental insights on axis selection by geometry.…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be essential to understand longer-scale perfect alignment on unpatterned substrates [4]. We also neglect potential couplings between cell shape and polarity [68][69][70], which can drive complex behaviors like cell circling and oscillation in response to fields, as observed in keratocytes [69]. We have neglected these factors because we have no evidence that fibroblasts show circular migration behavior similar to keratocytes.…”
Section: Broader Modeling Considerationsmentioning
confidence: 99%